RETRACTED: X-Linked Immunodeficient Mice With No Functional Bruton's Tyrosine Kinase Are Protected From Sepsis-Induced Multiple Organ Failure - O'Riordan, Caroline E.; Purvis, Gareth S. D.; Collotta, Debora; Krieg, Nadine; Wissuwa, Bianka; Sheikh, Madeeha H.; Ferreira Alves, Gustavo; Mohammad, Shireen; Callender, Lauren A.; Coldewey, Sina M.; Collino, Massimo; Greaves, David R.; et al. (Frontiers in Immunology, 2020)
We previously reported the Bruton’s tyrosine kinase (BTK) inhibitors ibrutinib and acalabrutinib improve outcomes in a mouse model of polymicrobial sepsis. Now we show that genetic deficiency of the BTK gene alone in Xid mice confers protection against cardiac, renal and liver injury in polymicrobial sepsis and reduces hyperimmune stimulation (‘cytokine storm’) induced by an overwhelming bacterial infection. Protection is due in part to enhanced bacterial phagocytosis in vivo, changes in lipid metabolism and decreased activation of NF-B and the NLRP3 inflammasome. The inactivation of BTK leads to reduced innate immune cell recruitment and a phenotypic switch from M1 to M2 macrophages, aiding in the resolution of sepsis. We have also found that BTK expression in humans is increased in the blood of septic non-survivors, while lower expression is associated with survival from sepsis. Importantly no further reduction in organ damage, cytokine production or changes in plasma metabolites is seen in Xid mice treated with the BTK inhibitor ibrutinib, demonstrating that the protective effects of BTK inhibitors in polymicrobial sepsis are mediated solely by inhibition of BTK and not by off-target effects of this class of drugs.